Weakly acidic reflux in patients with chronic unexplained cough during 24 hour pressure, pH, and impedance monitoring. Issue 4 (7th March 2005) - Sifrim, D; Dupont, L; Blondeau, K; Zhang, X; Tack, J; Janssens, J
Abstract : Background and aims: Acid gastro-oesophageal reflux is one of the most important causes of chronic cough. The response to acid suppression in these patients is not as good as in patients with heartburn but improvement with antireflux surgery has been reported, suggesting the involvement of a non-acidic gastric component in the refluxate. Less acidic reflux may produce symptoms such as regurgitation or chest pain. We investigated whether chronic cough might be associated with weakly acidic reflux. Methods: We studied 28 patients with chronic cough using 24 hour ambulatory pressure-pH-impedance monitoring. Manometry was used for precise recognition of cough and impedance-pHmetry to detect acid (pH <4), weakly acidic (pH 7–4), and weakly alkaline (impedance drops, pH ⩾7) reflux. A symptom association probability (SAP) analysis was performed for each type of reflux. Results: Analysis was completed in 22 patients with 24 cough events (5–92)/patient. The majority of cough events (69.4%) were considered "independent" of reflux whereas 30.6% occurred within two minutes of a reflux episode. Half of these (49%) were "reflux cough" sequences, involving acid (65%), weakly acidic (29%), and weakly alkaline (6%) reflux. Ten patients (45%) had a positive SAP between reflux and cough: five with acid, two with acid and weakly acidic, and three only with weakly acidic reflux. Conclusions: Ambulatory pressure-pH-impedance monitoring with SAP analysis allowed precise determination of the temporal association between cough and gastro-oesophageal reflux (acid, weakly acidic, and weakly alkaline) and identification of a subgroup of patients with chronic cough clearly associated with weakly acidic gastro-oesophageal reflux.